Rancang Bangun Media Storage Berbasis Armbian Menggunakan Orange-Pi dan Openmediavault - Widja, Ida Bagus Putu (Department of Electrical Engineering, University of Patria Artha, 2021)
Affordable smart phones and better camera capabilities have an impact on increasing photo and video capacity, not to mention the existence of social media content or online learning (the covid-19 pandemic), making the data growth rate fast enough every day so that data storage space on cellphones becomes full quickly. The problem occurs if the storage capacity is limited, forcing cellphone users to delete or move their data to another place so that the cellphone memory is more spacious. This data transfer process is often inefficient and the data will tend to be scattered in various places. To solve this problem, we propose a low-cost storage media server design that can facilitate the activity of transferring, backup or sharing data between devices wirelessly with various client models at home. The NAS (Network Attace Storage) server uses a Single Board Computer (SBC) device, namely the Orange-Pi One produced by Shenzhen Xunlong Software which uses an ARM Quad-core Cortex-A7 processor, 512MB of memory. NAS itself uses Openmediavault software that works on the Armbian Linux operating system. The test results of this media server system succeeded in sharing, backup and transfer of data easily and practically to one centralized storage.